2013
DOI: 10.1037/prj0000009
|View full text |Cite
|
Sign up to set email alerts
|

Healthy living? By whose standards? Engaging mental health service recipients to understand their perspectives of, and barriers to, healthy living.

Abstract: Health care professionals need to understand mental health service recipients' perspectives of a "healthy lifestyle." An understanding of barriers within this context is required, as only then will we be able to empathize and assist as health care professionals. This study also shows that realistic, innovative, and pragmatic solutions occur when mental health service recipients are empowered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…The focus groups directly engaged a community of mental health service users to help empower the community and individuals to develop health improvement initiatives. These focus groups were developed following on from initial research looking at service users perspectives of and barriers to healthy living [25]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus groups directly engaged a community of mental health service users to help empower the community and individuals to develop health improvement initiatives. These focus groups were developed following on from initial research looking at service users perspectives of and barriers to healthy living [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Barriers to engagement and continuance with such programs have been explored [2428] and researchers have identified that symptoms due to illness, treatment side effects, stigma (structural, social, and self), receiving little support, and difficulties changing habits all act as significant barriers to healthier lifestyle choices for mental health service users. Authors have also, however, highlighted the need to explore facilitators and factors that might aid individuals and program development to potentiate health behavior change [25, 29]. …”
Section: Introductionmentioning
confidence: 99%
“…Three different types of stigma have been identified as barriers to healthy living; structural stigma, social stigma and self-stigma (Graham, Griffiths, & Tillotson et al, 2013). Structural stigmas refer to how mental health services are organized often apart from general health care and decreasing availability to general health care among mental health service users.…”
Section: Master’s Level Mental Health Nursing Competencies In Terms Omentioning
confidence: 99%
“…Structural stigmas refer to how mental health services are organized often apart from general health care and decreasing availability to general health care among mental health service users. Social stigmas raise how mental health service users often are viewed in an undesirable way in society, and self-stigmas integrate all types of stigma leading to a negative self-image of incompetence among service users (Graham.et al, 2013). Significant barriers to physical activity among persons with mental health problems, beside symptoms of mental illness, medications and weight gain from medications, also include fear of discrimination and safety concerns (Nyeboe & Lund, 2013).…”
Section: Master’s Level Mental Health Nursing Competencies In Terms Omentioning
confidence: 99%
See 1 more Smart Citation